Munda Tribe Perception Towards Livelihood Through Sustainable Development - Kumari, Laxmi; Rahman, Mojibur (Problemy Ekorozwoju, 2021)
The purpose of the present study is to portray the perception of tribal communities towards sustainable development. The motive of the study is to picture the awareness which these tribal communities imbibe in themselves from primitive times. The idea to study Munda tribe of Jharkhand is because they are large in numbers, and will easily represent their outlook towards importance of preserving forest and livelihood development. The study focused on socio-capital and cultural understanding of the tribe in their livelihood. It emphasized on importance of women in the development of better livelihood. It showed how Non-Wood Forest Products (NWFP) are used in commercial and industrial form without affecting the natural resources, thus promotes sustainable development. The study also defined how through sustainable livelihood the tribe contributed in the revenue of the state government and also helped in generating income for the weaker section of the community.